Blurring the line between the DNA damage response and transcription: the importance of chromatin dynamics - Adam, Salomé (Exp Cell Res, 2014)
DNA damage interferes with the progression of transcription machineries. A tight coordination of transcription with signaling and repair of DNA damage is thus critical for safeguarding genome function. This coordination involves modulations of chromatin organization. Here, we focus on the central role of chromatin dynamics, in conjunction with DNA Damage Response (DDR) factors, in controlling transcription inhibition and restart at sites of DNA damage in mammalian cells. Recent work has identified chromatin modifiers and histone chaperones as key regulators of transcriptional activity in damaged chromatin regions. Conversely, the transcriptional state of chromatin before DNA damage influences both DNA damage signaling and repair. We discuss the importance of chromatin plasticity in coordinating the interplay between the DDR and transcription, with major implications for cell fate maintenance.